Utilization of catfish (Clarias gariepinus) dregs fish bone gelatin extraction on mango (Mangifera indica L.) fruit leather product: Pemanfaatan tepung limbah ekstraksi gelatin tulang ikan lele (Clarias gariepinus) pada produk fruit leather mangga (Mangifera indica L.) - Kiptiyah, Sakina Yeti; Hakim, Najmi Ardinur; Amelianawati, Mae (JITIPARI, 2025)
Catfish dregs fish bone gelatin extraction still has the potential to be utilized by processing it into flour. Catfish dregs fish bone gelatin extraction can be used as an additional source of calcium in mango fruit leather products. This study goals to know the effect of adding catfish bone meal on the chemical also organoleptic characteristics of mango fruit leather. This study used a CRD with a single factor, the addition of catfish bone gelatin waste flour with 5 levels of treatment, including; P0 (control), P1 (2.5 grams), P2 (5 grams), P3 (7.5 grams), also P4 (10 grams). The variables observed included water content, reducing sugar content, vitamin C content, calcium content also organoleptic properties (color, aroma, texture, taste also overall). The results of adding catfish bone flour had a significant effect on fruit leather moisture, vitamin c, also calcium levels (p <0.05). Treatment P4 produced the best results, especially in terms of water content, vitamin C content also calcium content, while P2 was the best treatment in terms of organoleptic parameters. The results of the chemical characteristics with the best treatment had a vitamin C content of 51.3 mg/100, a water content of 12.6% (ww) and a calcium content of 1.82% and from organoleptics an overall score of 3.77.